An in vitro model of mesenchymal stem cell targeting using magnetic particle labelling. (27th December 2012) - El Haj, Alicia J.; Glossop, John R.; Sura, Harpal S.; Lees, Martin R.; Hu, Bin; Wolbank, Susanne; van Griensven, Martijn; Redl, Heinz; Dobson, Jon
Abstract The specific targeting of cells to sites of tissue damage in vivo is a major challenge precluding the success of stem cell‐based therapies. Magnetic particle‐based targeting may provide a solution. Our aim was to provide a model system to study the trapping and potential targeting of human mesenchymal stem cells (MSCs) during in vitro fluid flow, which ultimately will inform cell targeting in vivo. In this system magnet arrays were used to trap superparamagnetic iron oxide particle‐doped MSCs. The in vitro experiments demonstrated successful cell trapping, where the volume of cells trapped increased with magnetic particle concentration and decreased with increasing flow rate. Analysis of gene expression revealed significant increases in COL1A2 and SOX9. Using principles established in vitro, a proof‐of‐concept in vivo experiment demonstrated that magnetic particle‐doped, luciferase‐expressing MSCs were trapped by an implanted magnet in a subcutaneous wound model in nude mice. Our results demonstrate the effectiveness of using an in vitro model for testing superparamagnetic iron oxide particles to develop successful MSC targeting strategies during fluid flow, which ultimately can be translated to in vivo targeted delivery of cells via the circulation in a variety of tissue‐repair models. Copyright © 2012 John Wiley & Sons, Ltd.